INFORMATION SECURITY OF CHILDREN IN LAY THINKING OF PARENTS AND TEACHERS - I B Bovina; N V Dvoryanchikov; S V Budykin (Peoples' Friendship University of Russia (RUDN University), 2016)
The problem of the information security of children is discussed in the presented paper. A special attention is paid to the Internet as a risk source. The article gives evidence to the importance of the analysis of the so called lay thinking about the information security of children. The presented study is based on the social representations theory proposed by S.Moscovici. The total of the study is 136 people (parents and teachers), aged from 21 to 62 years old. We supposed that the lay thinking about the information security in groups of parents and teachers was formed on two main themes - about the threats and about the ways to manage these threats. Also we supposed that parents and teachers had similar thinking about the threats but differed in their thinking about the way to manage the threat. The suppositions got partial empirical support.